The influence of vocabulary size and the use of reading techniques in the level of reading comprehension of students who are taking Reading and Conversation I course at the Foreign Languages Department of the School of Arts and Sciences of the University of El Salvador during the second semester of 2013 - Madrid Hernández, Alma Noheli
English is a worldwide language; so many investigations have been done about this language. Many scholars have written books about English as a second language and books for teaching English but these investigations have been carried out in diverse countries with contexts totally different from the ones that Salvadorian students live in. This research has been conducted with the objective of providing sources to future English learners with Salvadorian contexts especially for the reality of the Foreign Languages Department of the Arts and Sciences School of the University of El Salvador; so that students of the foreign Language Department can have access to researches done in their own context. This study was aimed at determining how influential vocabulary size and the use of reading techniques are in reading comprehension. The research question was “How do vocabulary size and the use of reading techniques influence reading comprehension of students who are taking Reading and Conversation I course at the Foreign Languages Department of the Arts and Sciences School of the University of El Salvador?”. In this research, three main aspects of students‟ skill profile were taken into account: Vocabulary level, the use of reading techniques and the level of reading comprehension. In order to collect the data, the instruments selected for this research were three different tests. The first one, a vocabulary test from Cambridge University Press. The second, a test for identifying the use of reading techniques that was designed by the researchers taking into account different sources. And the last one, a reading comprehension test designed by Cambridge University Press. These tests were administered to 62 out of 78 students that were taking the Reading and Conversation I course of the Foreign Language Department of the Arts and Sciences School of the University of El Salvador during the second semester of 2013. After administering the tests, the students‟ results of each test were divided into subcategories in order to organize the information gathered. Those categories were established by the grade that students obtained in each test. This organization helped researches to analyze the data for answering the research question. Microsoft Excel was used for the statistical procedure. Line graphs were done for representing the data so that researches could interpret the results for achieving the conclusions of the research. The conclusions of this research are going to be helpful not only for students but also for teachers since it gives an overview of the impact that vocabulary level and the use of reading techniques have on students‟ reading comprehension. Since this research has been carried out at the Foreign Language Department of Arts and Science School of the University of El Salvador.